The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/ijerph191912399
|View full text |Cite
|
Sign up to set email alerts
|

Ecosystem Health Responses of Urban Agglomerations in Central Yunnan Based on Land Use Change

Abstract: Land use change in urban agglomerations is gradually becoming a major cause and a key factor of global environmental change. As a consequence of the interaction between land use and ecological processes, the transformation in natural ecosystem structure and function with human activity disturbances demands a systematic assessment of ecosystem health. Taking the Central Yunnan urban agglomeration, undergoing transition and development, as an example, the current study reveals the typical land use change process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 51 publications
(51 reference statements)
0
2
0
Order By: Relevance
“…This trend corresponds with findings from previous research [47]. In general, the region has experienced rapid economic development and an accelerated urbanization process [48] over the past twenty-five years. This has led to a substantial demand for construction land to support urban expansion and industrial development, prompted by a significant population influx, requiring extensive residential and urban infrastructure.…”
Section: Analysis Of Changes In Land Usesupporting
confidence: 91%
“…This trend corresponds with findings from previous research [47]. In general, the region has experienced rapid economic development and an accelerated urbanization process [48] over the past twenty-five years. This has led to a substantial demand for construction land to support urban expansion and industrial development, prompted by a significant population influx, requiring extensive residential and urban infrastructure.…”
Section: Analysis Of Changes In Land Usesupporting
confidence: 91%
“…In maintaining the synchronization of environmental protection and economic development, we focus on optimizing the regional development pattern, reasonably allocating ecological, living, and production spaces, and reducing the negative effects of human development on the ecological environment [78]. On the other hand, the landscape ecological risk assessment with land use change as the causal factor is incorporated into the land use planning process, the unique natural conditions and landscape pattern characteristics of mountainous areas are recognized, land macro-control is strengthened, land use optimization and improvement are systematically carried out, the level of land protection and intensive use is improved [79], and different ecological restoration measures and intensities are applied to different vegetation areas to achieve ecosystem function Maximization [80], to attenuate the sensitivity of topographic gradients to ecological risk impacts.…”
Section: Policy Impact Of Regional Developmentmentioning
confidence: 99%
“…Changes in land use and cover significantly affect ecosystem health. Chen [11] and Gao [12] pinpoint urban expansion and land transfer as key influencers. Yu et al found that urban expansion, along with farmland protection policies, can harm ecological quality [13], while Chen et al identified the critical role of forests and hydrological systems in ecosystem services [14].…”
Section: Introductionmentioning
confidence: 99%